2017
DOI: 10.1007/978-1-4939-7463-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Methods for Reconstructing Ancient Genome Organization

Abstract: Comparative genomics considers the detection of similarities and differences between extant genomes, and, based on more or less formalized hypotheses regarding the involved evolutionary processes, inferring ancestral states explaining the similarities and an evolutionary history explaining the differences. In this chapter, we focus on the reconstruction of the organization of ancient genomes into chromosomes. We review different methodological approaches and software, applied to a wide range of datasets from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…Most popular methods for reconstructing the ancestral genome architecture follow one of two strategies: either they make use of a genome rearrangement model to derive parsimonious rearrangement scenarios that explain the observed differences in modern genome architectures, or they infer syntenic blocks. These constitute conserved neighborhoods of individual pairs of markers, also denoted adjacencies, or neighborhoods of marker sets comprising more than two markers [6].…”
Section: Related Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most popular methods for reconstructing the ancestral genome architecture follow one of two strategies: either they make use of a genome rearrangement model to derive parsimonious rearrangement scenarios that explain the observed differences in modern genome architectures, or they infer syntenic blocks. These constitute conserved neighborhoods of individual pairs of markers, also denoted adjacencies, or neighborhoods of marker sets comprising more than two markers [6].…”
Section: Related Methodsmentioning
confidence: 99%
“…Alternative methods such as PMAG [15] and DeCoStar [16] use likelihood estimation to infer ancestral gene orders, yet are limited to process adjacencies only. Nevertheless, DeCoStar infers evolutionary trees of marker adjacencies and therefore can handle evolutionary events such as duplication, insertion, and loss [6].…”
Section: Model-based Reconstruction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have been used in many other elds of computational biology, such as scaolding [2], reference guided genome assembly [183], phylogenomics [279], and cancer genomics [384]. Comprehensive reviews of genome rearrangement models and its applications can be found in [113,142,383,15,144,311].…”
Section: Genome Rearrangementsmentioning
confidence: 99%
“…Up to now, biological computation techniques have been developed to solve a variety of problems, but when it comes to solve specic problems in computational biology, these techniques are mainly designed as sequential methods, handling manageable data sizes, or as distributed methods, handling big biological data while making use of the emerging new parallel infrastructures. On the other hand, only a limited number of bioinformatics software (that we also call software biology tools") are making use of the parallel frameworks, while properly 15 https://cme.h-its.org/exelixis/software.html/ 16 to a new challenge in biological computation that requires further attention from computer scientists, statisticians, and mathematicians. The sought biological software tools, that we can call a second generation of biological software tools , need to be reusable and portable.…”
Section: Highlightsmentioning
confidence: 99%